2016
DOI: 10.1099/mic.0.000200
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of eukaryotic serine racemases in the bacterial domain and characterization of a representative protein in Roseobacter litoralis Och 149

Abstract: Two distinct bacterial and eukaryotic serine racemases (SRs) have been identified based on phylogenetic and biochemical characteristics. Although some reports have suggested that marine heterotrophic bacteria have the potential to produce D-serine, the gene encoding bacterial SRs is not found in those bacterial genomes. In this study, using in-depth genomic analysis, we found that eukaryotic SR homologues were distributed widely in various bacterial genomes. Additionally, we selected a eukaryotic SR homologue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Microbiological and geochemical studies suggested the microbial production and consumption of DAAs in pelagic water ecosystems (Perez et al, 2003 ; Teira et al, 2006 ; Calleja et al, 2013 ; Zhang et al, 2016 ). In this geochemical cycle, importance of marine Alphaproteobacteria in the production of DAAs has already been pointed out (Pedersen et al, 2001 ; Lomstein et al, 2006 ; Kaiser and Benner, 2008 ; Kubota et al, 2016 ), however, phylogenetic and physiological features of DAA-utilizing marine bacteria are poorly investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiological and geochemical studies suggested the microbial production and consumption of DAAs in pelagic water ecosystems (Perez et al, 2003 ; Teira et al, 2006 ; Calleja et al, 2013 ; Zhang et al, 2016 ). In this geochemical cycle, importance of marine Alphaproteobacteria in the production of DAAs has already been pointed out (Pedersen et al, 2001 ; Lomstein et al, 2006 ; Kaiser and Benner, 2008 ; Kubota et al, 2016 ), however, phylogenetic and physiological features of DAA-utilizing marine bacteria are poorly investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…R F value of the separated spots was calculated by using L-serine as a reference compound and the given formula: RP-HPLC-For the HPLC analysis, reverse-phase C-18 column (Agilent, C-18, X 4.6mm, 5um) and Agilent (1220 In nity II LC) HPLC system. Gradient elution was applied as described elsewhere with further modi cations [25]. The solvent system was set as: A. sodium acetate (pH 6.5, 40mM); B. methanol: acetonitrile (30:70).…”
Section: Chromatographic Analysis Of the Enantiomersmentioning
confidence: 99%
“…RP-HPLC-For the HPLC analysis, reverse-phase C-18 column (Agilent, C-18, 250 X 4.6mm, 5um) and Agilent (1220 In nity II LC) HPLC system. Gradient elution was applied as described elsewhere with further modi cations [25]. The solvent system was set as: A. sodium acetate (pH 6.5, 40mM); B.…”
Section: Chromatographic Analysis Of the Enantiomersmentioning
confidence: 99%
“…Howbeit, our knowledge in the case of prokaryotic SRs is still constrained. For instance, the synthesis of D-serine in marine heterotrophs is unstable and inhibits the bacterial growth of Roseobacter litoralis Och 149 [25]. In Enterococcus gallinarum BM4174, Alanine racemase is known to synthesize D-serine which is the further precursor of PG of this Gram-positive bacteria [13].…”
Section: Introductionmentioning
confidence: 99%